2021
DOI: 10.32394/rpzh.2021.0163
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition habits and frequency of consumption of selected food products by the residents of urban and rural area from the Subcarpathian voivodeship

Abstract: Background. The dynamic development and change of rural lifestyle patterns towards urban patterns has been noticeable since the second half of the 20th century. Nutrition, as well as the lifestyle in urban and rural areas, has undergone a process of urbanization, which is evidenced by the following an increasing number of overweight people. Objective. The aim of the study was to compare eating habits and frequency of consumption of selected groups of products between the urban and rural residents from the Subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Research by Szałajko et al (2021) indicates that the disparities in food consumption between rural and urban areas are influenced by factors such as education and socioeconomic status. Diversity in food consumption is very important, which becomes a factor affecting overweight and stunting for children (Hatløy et al, 2000), lack of diversity in food consumption can promote health problems (Ding & Kinnucan, 2011).…”
Section: Results and Discussion The Descriptive Household Income And ...mentioning
confidence: 99%
“…Research by Szałajko et al (2021) indicates that the disparities in food consumption between rural and urban areas are influenced by factors such as education and socioeconomic status. Diversity in food consumption is very important, which becomes a factor affecting overweight and stunting for children (Hatløy et al, 2000), lack of diversity in food consumption can promote health problems (Ding & Kinnucan, 2011).…”
Section: Results and Discussion The Descriptive Household Income And ...mentioning
confidence: 99%
“…However, our study did not confirm an association between education and the intention to eat less meat. Previous studies conducted in Poland have also shown that there is no relationship between education and the consumption of red meat, poultry, and cold cuts [ 77 ], but also that the relationship varies between men and women [ 73 ]. Unlike eating less meat, a positive relationship was shown between education and intention to eat more plant-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the frequency of consumption of selected products carried out in 2019 in one region in Poland—the Subcarpathian voivodeship—also showed that poultry was consumed more often than red meat [ 47 ]. This could also be explained as a result of price increases for red meat and changes in eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned study in the Subcarpathian voivodeship showed that the village inhabitants more often mainly consumed staple foods, such as cereals and potatoes. In the case of meat, there were significant differences for cold cuts, which were eaten more often in rural than in urban areas [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation